2015
DOI: 10.1111/ncmr.12050
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Business Negotiations Using Practitioner Data

Abstract: Although negotiations are a core business activity, there is a lack of information about what actually occurs during a business negotiation. This study addresses this issue though an international survey of managers focusing on actual negotiations. The 294 respondents reported on what actions they took as they sought to achieve an agreement, including how information was exchanged and how they looked for new solutions and managed concession making. The analysis suggests a pragmatic approach to negotiation, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…As an example, in a situation where two companies had committed to cooperate over sharing resources, the negotiations themselves were still competitive (Fells, 2013). Both Fells et al (2015) and Ramsay (2004) found an underlying competitiveness as evidenced in their surveys of business and supply chain negotiations.…”
Section: Exploring the Role Of Negotiation In Supplier Relationship Mmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, in a situation where two companies had committed to cooperate over sharing resources, the negotiations themselves were still competitive (Fells, 2013). Both Fells et al (2015) and Ramsay (2004) found an underlying competitiveness as evidenced in their surveys of business and supply chain negotiations.…”
Section: Exploring the Role Of Negotiation In Supplier Relationship Mmentioning
confidence: 99%
“…The interviews with the 36 senior procurement managers provide rich insights into how they manage their buyer-supplier relationships and, in particular, into the role of negotiations. As in any other context, buyer-supplier negotiations occur only because neither party is able to achieve its objectives without the involvement of the other (Fells, 2016). The ensuing negotiations not only set the terms of the contract but also establish the context in which the contract will be implemented.…”
Section: Analysis: the Experience Of Practitioners The Initial Negotimentioning
confidence: 99%
“…Media coverage can contribute to an integrative approach to conflict and negotiation, but it may not always be in the interest of boosting newspaper ratings. The negotiation processes of 294 practitioners were analyzed to unravel the pragmatic strategies used to arrive at agreements (Fells, Rogers, Prowse, & Ott, ). That study, however, noted the need for further research into the pressures and context which impact negotiators' decision‐making.…”
Section: Discussionmentioning
confidence: 99%
“…The party, which had the lower hand at the time of the negotiation and agreement, will later struggle to improve its stand and will pull out (or, at least, tend to pull out) of the agreement with party which at that time had the upper hand. In the context of this viewpoint and further commenting on effective negotiation process, Fells et al (2015) state that fuller exchange and sharing of information and data and openly exchanging each party's goals and "the ideal" solution and then sincerely working out an acceptable compromise accord would result in a more realistic and satisfying solution to both parties.…”
Section: Challenges In Negotiationmentioning
confidence: 99%